Facilitator and Barrier to Health Information System Use from Health Professionals Perspective: A Scoping Review - Yuliasih N; Khoiry QA; Alfian SD; Suwantika AA; Abdulah R (Journal of Multidisciplinary Healthcare, 2025)
Nur Yuliasih,1 Qisty A Khoiry,1 Sofa D Alfian,1– 3 Auliya A Suwantika,1– 3 Rizky Abdulah1,2 1Department of Pharmacology and Clinical Pharmacy, Faculty of Pharmacy, Universitas Padjadjaran, Jatinangor, Indonesia; 2Drug Utilization and Pharmacoepidemiology Research Group, Center of Excellence for Pharmaceutical Care Innovation, Universitas Padjadjaran, Jatinangor, Indonesia; 3Center for Health Technology Assessment, Universitas Padjadjaran, Jatinangor, IndonesiaCorrespondence: Sofa D Alfian, Department of Pharmacology and Clinical Pharmacy, Faculty of Pharmacy, Universitas Padjadjaran, Jl. Raya Jatinangor, KM 21, Jatinangor, Sumedang, Indonesia, Tel/Fax +62-022-7796200, Email sofa.alfian@unpad.ac.idObjective: This study aimed to present factors that potentially influenced system use by identifying facilitator or barrier to acceptance from the perspective of healthcare professionals.Methods: A scoping review was used in line with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR) guidelines. The literature search was conducted on two electronic databases, Scopus and MEDLINE through PubMed, limiting the publication timeframe from January 2013 to December 2023. Moreover, a developed search strategy was used based on keywords and MeSH terms derived from the Population, Concept, and Context (PCC) components. The inclusion criteria were studies that discussed information system in healthcare, incorporated healthcare professionals who directly engaged with health information system (HIS), conducted within healthcare settings, identified facilitator or barrier to the use of information system in healthcare, and were available in full-text English. Barrier and facilitator were considered as factors impeding and promoting HIS use, respectively. The scoping review adopted a thematic analysis.Results: The results showed that a total of 79 studies met the inclusion criteria and were included in this review. A total of 16 distinct facilitators and 16 barriers were identified, which were then grouped into four categories, comprising colleague and social support, organizational, individual, as well as technological and technical contexts. The most frequently mentioned facilitator was usefulness and simplification of daily tasks, while the predominant barrier was lack of technical support.Conclusion: The systematic mapping of facilitator and barrier provided a foundation for policymakers and healthcare professionals in decision-making processes to enhance acceptance HIS.Keywords: health information system, health professionals, facilitator, barrier, electronic health record